Is there a connection between ESG scores and a company’s profitability? Empirical evidence on selected Stoxx Europe 600 firms - Hussam Musa; Peter Krištofik; Yaroslav Lysenko; Juraj Medzihorsky (Investment Management & Financial Innovations)
This study scrutinizes the potential correlation between Environmental, Social, and Governance (ESG) scores and the profitability of firms listed in the selected STOXX Europe 600 index. Utilizing panel regression analysis, the study examines data from 385 non-financial companies over the period 2017 to 2021, correlating CSRHub's ESG scores and selected financial variables with corporate profitability measured by ROA. The investigation reveals that, overall, ESG scores do not have a significant impact on profitability, except for the ESG-community sub-score, which shows a slight negative influence. Thus, this paper partially supports studies that show a negative correlation between ESG and profitability, even though such results are in the minority in the literature. The overall results suggest that while ESG scores may reflect a company's ethical stance, they are not a predominant factor influencing its profitability. However, this is not the case for leverage, as the importance of capital structure for profitability is confirmed. AcknowledgmentThis research has been supported by the Scientific Grant Agency of the Slovak Republic under project VEGA No. 1/0579/21.